Assessment of the Activity of Lactate Dehydrogenase, Gamma-glutamyl Transpeptidase and Alkaline Phosphatase in Breast Cancer Patients with and without Lymph Node Metastasis - abubakr, muzdalifa; A. Ahmed, Zahra; A. Abdrabo, AbdElkarim (مجلة الجزيرة للعلوم الصحية; مجلد 15 عدد 1 (2019), 2019)
Background: Breast cancer has the highest cancer incidence in women and is one of the leading causes of mortality globally. Lactate dehydrogenase (LDH) and other enzymes are vital metabolic enzymes that are associated with cancer development, invasion, and metastasis. Aim: The present study aimed to evaluate the LDH, Gamma-glutamyl transpeptidase (GGT) and Alkaline phosphatase (ALP) levels in the circulation of patients of breast cancer in different stages and tried to correlate levels with the disease stage and duration of breast cancer with and without lymph node involvement. Methods: LDH, GGT, and ALP were analyzed by means of the spectrophotometer, Biosystem device and reagents, serum samples were used for measurement. Results : GGT and LDH had a significant difference with P.value 0.022 and 0.001 respectively between stages II and III, while ALP didn't show a significant difference. Conclusion: This data concluded that enzyme markers like serum LDH and GGT could be sensitive, specific and cost effective biomarkers for diagnosing carcinoma of the breast and for monitoring its progression